(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Ultra-low frequency (ULF) geomagnetic analysis is a robust method for earthquake (EQ) forecasting. We conducted a simultaneous study of EQ precursors around the western part of Java Island in 2020 using wavelet transform (WT) and detrended fluctuation analysis (DFA) methods. ULF geomagnetic data (March to December 2020, 16:00–21:00 UTC or 23.00–04.00 LT) from Lampung Selatan (LPS) geomagnetic station were used to assess the precursors. We analyzed four EQs with an epicenter distance (R) of around 100 km from LPS station and a magnitude (M) greater than 5 Mw. We analyzed changes in the SZ/SG values and α values from the WT and DFA analyses against the threshold (µ±2σ) to identify anomalies related to the EQs. The result showed that SZ/SG anomalies occurred simultaneously with a decrease in α values several weeks prior to probable source EQ when there was a very low geomagnetic activity (Dst ≤ -30 nT). The Mw5.4 (07/07/2020) EQ might be the main source that led to the appearance of the precursor since it had the highest magnitude and KLS values compared to others. The combined WT and DFA results showed anomalies 1.5–13 weeks before the Mw5.4 (07/07/2020) EQ. The results suggest that WT and DFA are suitable methods for detecting EQ precursors but more work is needed to link the precursors to specific EQs.